Disinfectant wipes are appropriate to control microbial bioburden from surfaces: use of a new ASTM standard test protocol to demonstrate efficacy. Issue 4 (December 2015) - Sattar, S.A.; Bradley, C.; Kibbee, R.; Wesgate, R.; Wilkinson, M.A.C.; Sharpe, T.; Maillard, J-Y.
Summary: Background: The use of disinfectant pre-soaked wipes (DPW) to decontaminate high-touch environmental surfaces (HTES) by wiping is becoming increasingly widespread in the healthcare environment. However, DPW are rarely tested using conditions simulating their field use, and the label claims of environmental surface disinfectants seldom include wiping action. Aim: To evaluate the new E2967-15 standard test specific to wipes, particularly their ability to decontaminate surfaces and to transfer acquired contamination to clean surfaces. Methods: ASTM Standard E2967-15 was used by three independent laboratories to test the efficacy of five types of commercially available wipe products. All data generated were pulled together, and reproducibility and repeatability of the standard were measured. Findings: All the commercial DPW tested achieved a >4 log10 (>99.99%) reduction in colony-forming units (CFU) of Staphylococcus aureus and Acinetobacter baumanii with 10 s of wiping, but only one DPW containing 0.5% accelerated H2 O2 prevented the transfer of bacteria to another surface. Conclusion: This newly introduced standard method represents a significant advance in assessing DPW for microbial decontamination of HTES, and should greatly assist research and development, and in making more relevant and reliable claims on marketed DPW.